2013
DOI: 10.1016/j.jvs.2012.06.098
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day vein remodeling is predictive of midterm graft patency after lower extremity bypass

Abstract: OBJECTIVES Successful adaptation of a vein graft to an arterial environment is incompletely understood. We sought to investigate whether early vein graft remodeling is predictive of subsequent patency. METHODS A prospective longitudinal study of 67 patients undergoing lower extremity bypass with autologous vein between February 2004 and April 2008. Preoperative blood samples were drawn for biomarkers. During the bypass operation, a 5 cm index segment of the graft was registered for serial lumen diameter meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
3
33
1
Order By: Relevance
“…Gasper et al demonstrated that early remodeling was predictive of late vein graft failure [25]. If translated to the clinical setting, our results suggest that external support is likely to increase long-term graft patency.…”
Section: Resultssupporting
confidence: 59%
“…Gasper et al demonstrated that early remodeling was predictive of late vein graft failure [25]. If translated to the clinical setting, our results suggest that external support is likely to increase long-term graft patency.…”
Section: Resultssupporting
confidence: 59%
“…To test this hypothesis, we initiated a prospective cohort study to systematically determine remodeling characteristics of lower extremity bypass grafts over the first year of implantation. [20-23] Employing high-resolution ultrasound images, luminal and wall changes were characterized from a defined region of the vein graft. We also employed pulse wave velocity (PWV) analysis to determine stiffness changes in the vein over time.…”
Section: The Remodeling Of Human Vein Bypassmentioning
confidence: 99%
“…[25, 26] Specifically, African American race was associated with less positive remodeling over the first month of implantation and vein grafts implanted in these patients never achieved the diameter of those in Caucasians. [23] Just as importantly diabetes mellitus, hypertension, and hyperlipidemia were not associated with remodeling; none of which have been shown to be associated with reduced patency of lower extremity vein grafts.…”
Section: The Remodeling Of Human Vein Bypassmentioning
confidence: 99%
See 1 more Smart Citation
“…In vein bypass grafts, an early adaptive remodeling occurs in response to increased shear stress and wall tension, resulting in overall vessel enlargement and increased wall thickness. 85,86 If the hyperplastic response continues, or is accompanied by a constrictive fibrosis, stenosis may ensue. Vein graft stenosis is most typically focal, for example, in the perianastomotic regions and at valve sites; more rarely it occurs diffusely throughout the graft.…”
Section: Control Of Neointimal Hyperplasiamentioning
confidence: 99%